1992
DOI: 10.1002/1097-4679(199203)48:2<233::aid-jclp2270480215>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The comparative concurrent validities of the Shipley Institute of Living Scale and the Henmon-Nelson Tests of Mental ability

Abstract: This study compared the abilities of the Shipley Institute of Living Scale and the Henmon‐Nelson Tests of Mental Ability to predict Wechsler Adult Intelligence Scale‐Revised (WAIS‐R) scores in psychiatric hospital patients. The Henmon‐Nelson DIQs accounted for about 50% more WAIS‐R Verbal and Full Scale IQ variance than did the Shipley IQs, apparently because of their higher correlations with the Information, Vocabulary, and, perhaps, Similarities subtests. Because Henmon‐Nelson scores were more variable and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Henmon-Nelson raw scores have been shown to correlated strongly with standard intelligence measures, such as WAIS Full Scale IQ scores (Watson et al, 1992; Watson et al, 1981). Participants completed this test during high school, and scores were obtained from the Wisconsin State Testing Service.…”
Section: Methodsmentioning
confidence: 99%
“…Henmon-Nelson raw scores have been shown to correlated strongly with standard intelligence measures, such as WAIS Full Scale IQ scores (Watson et al, 1992; Watson et al, 1981). Participants completed this test during high school, and scores were obtained from the Wisconsin State Testing Service.…”
Section: Methodsmentioning
confidence: 99%
“…Inductive ability was inferred from scores on the 20-item Abstraction subtest. The SILS is a commonly used, easily administered intelligence test (Watson et al, 1992) that correlates favorably with Wechsler Adult Intelligence Scale-Revised subscales (range = .68-.90; Zachary, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…SILS has been used for more than 50 years to assess facets of intelligence and to establish its reliability and validity (Zachary, 1991). Several research studies provided support for SILS’ validity as a brief measure of intelligence (Martin, Blair, & Bledsoe, 1990; Watson et al, 1992). Research has also found that performance on the Shipley is significantly correlated with performance on the Wechsler Adult Intelligence Scale–Revised (Weiss & Schell, 1991; Zachary, Paulson, & Gorsuch, 1985).…”
Section: Methodsmentioning
confidence: 99%